Diagnostic accuracy of physical examination tests in core muscle injury - Kurowicki, J.; Kraeutler, M. J.; Castrodad, I. M. D.; Hahn, A. K.; Simone, E. S.; Kelly, M. A.; Talishinskiy, T.; Scillia, A. J. (The American Journal of Sports Medicine, 2020)
Background: Core muscle injury (CMI), often referred to as a sports hernia, is a common cause of groin pain in athletes characterized by concomitant injury to the insertion of the adductor longus and the rectus abdominis muscles. Currently, the literature on CMI is sparse with no standardized physical examination tests used in the diagnosis of this type of injury.